Serhiy Oleksandrovych Khmyzov - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The article is dedicated to the 60th birthday of the head of the Department of Pathology of the Spine and Joints of Children of the State Institution «Sytenko Institute of Spine and Joint Pathology of the National Academy of Medical Sciences of Ukraine», Doctor of Medical Sciences Professor Khmyzov S. А.